Management and Development of Government Officials Performance Competency, the Excise Department - Suphaphot, Erika; Charoenputh, Vorsit (Legal State Journal, 2024)
This research article aims to evaluate the management and development of government officials’ performance competency of the Excise Department; to describe a correlation between government officials performance competency and the management and development of performance competency; and to propose guidelines for management and development of government officials’ performance competency of the Excise Department. This study employed a quantitative approach. The sample consisted of 388 government officials working for the Excise Department, the Ministry of Finance. Data was collected through questionnaires. Statistics used to analyze the data were frequency, percentage, mean, standard deviation, Pearson’s product moment correlation coefficient analysis and multiple regression analysis. Findings are as follows: (1) On the analysis of the management and development of government officials’ performance competency, it was found that the management and development was at the highest level. (2) The relationship between the management of the competency development of civil servants in the Excise Department and the factors affecting the management of the competency development of civil servants in the Excise Department had a positive relationship with statistical significance at the .01 level. (3) The factors affecting the management of the performance competency of the Excise Department can predict and present the management model of the performance competency of the Excise Department with an effect of more than 30 percent, while the rest are other factors.